Encyclopedia of violence, peace, & conflict - Kurtz, Lester R. (Elsevier, 2008)
Provides timely and useful information about antagonism and reconciliation in all contexts of public and personal life. An essential reference for students and scholars working in the field of peace and conflict resolution studies, and for those seeking to explore alternatives to violence and share visions and strategies for social justice and social change.